2019
DOI: 10.1177/1077559519893471
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing in Child Welfare Services: A Systematic Review

Abstract: Families in the child welfare (CW) system who cannot be engaged in services are at high risk of negative outcomes. As motivational interviewing (MI) has been shown to improve engagement in similar contexts. This study aimed to systematically review MI with CW families as well as MI training with CW workers and social work students training to become CW workers. The review used Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and searched multiple databases in June 2018. In Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Wells & Jones (Wells & Jones, 2018) showing that MI helps teachers create a learning environment based on cooperativeness, empowerment, participation and motivation, and with the understanding of the emotional dimension of learning. Moreover, the results are inconsistent with those of Ashouri et al (Ashouri et al, 2015) showing that MI is effective in increasing self-efficacy and self-concept of low-achieving high school students and with those of Hall, Sears & Walton (Hall et al, 2020) that showed that teaching MI to welfare organization staff leads to increased self-efficacy. The results were also inconsistent with those of McCabe et al (McCabe et al, 2019) that showed using MI in people with OCD undergoing ERP treatment enhances self-efficacy, leads to greater adherence to treatment, and consequently reduces symptoms and treatment stability.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Wells & Jones (Wells & Jones, 2018) showing that MI helps teachers create a learning environment based on cooperativeness, empowerment, participation and motivation, and with the understanding of the emotional dimension of learning. Moreover, the results are inconsistent with those of Ashouri et al (Ashouri et al, 2015) showing that MI is effective in increasing self-efficacy and self-concept of low-achieving high school students and with those of Hall, Sears & Walton (Hall et al, 2020) that showed that teaching MI to welfare organization staff leads to increased self-efficacy. The results were also inconsistent with those of McCabe et al (McCabe et al, 2019) that showed using MI in people with OCD undergoing ERP treatment enhances self-efficacy, leads to greater adherence to treatment, and consequently reduces symptoms and treatment stability.…”
Section: Discussioncontrasting
confidence: 63%
“…The results of Ashrafzadeh et al (Ashrafzadeh et al, 2017) indicated that MI training has had a significant impact on academic self-efficacy and problem solving of female high school students. Hall, Sears & Walton (Hall et al, 2020) concluded that MI training to welfare organization employees increased self-efficacy and empathy in them. Strait, Williams & Peters (Strait et al, 2019) showed that MI improved student academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some graduate-level social work programs are already training students for MI practice (Barth et al, 2017;Iachini, Lee, DiNovo, Lutz, & Frey, 2018;Pecukonis et al, 2016) (Corcoran, 2016;Hohman, 2012). In addition, there are videos specific to training MI in CW developed by the University of Minnesota and University of California, Davis (Hall & Hohman, 2012). Moreover, collaborative partnerships similar to those described by Iachini and colleagues at the University of South Carolina (2018) could be developed with Motivational Interviewing Network of Trainers, which hosts live and self-paced online training courses.…”
Section: Discussionmentioning
confidence: 99%
“…Dauber and colleagues (2017) expressed that some of these approaches may be used to improve the implementation in future trials. For example, Hall and Hohman (2012) provide a manual specifically on applying MI to CW settings, which is available at no cost along with corresponding videos online. Given the results of Forrester et al (2018), more research is needed on the amount of MI training and supervision needed to improve skills as well as possible CW outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, many clients have ambivalence about services and treatments, with part of them moving towards change and another part of them resisting change. Practitioners need strategies to support clients in moving towards change, such as those offered by motivational interviewing ( 75 ). Third, while a working alliance is a consistent mediator of change ( 76 , 77 ), including in contexts where treatment is mandated [for example, by child welfare ( 78 )], difficulties with alliance between providers and clients should be anticipated and problem-solved in child welfare work.…”
Section: Case Conceptualization: Definition and Componentsmentioning
confidence: 99%